How can dementia and disability be prevented in older adults: where are we today and where are we going?. (10th January 2021) - Lisko, I.; Kulmala, J.; Annetorp, M.; Ngandu, T.; Mangialasche, F.; Kivipelto, M.
Abstract: Ageing of the population, together with population growth, has brought along an ample increase in the number of older individuals living with dementia and disabilities. Dementia is the main cause of disability in old age, and promoting healthy brain ageing is considered as a key element in diminishing the burden of age‐related disabilities. The World Health Organization recently launched the first risk reduction guidelines for cognitive impairment and dementia. According to recent estimates, approximately 40% of dementia cases worldwide could be attributable to 12 modifiable risk factors: low education; midlife hypertension and obesity; diabetes, smoking, excessive alcohol use, physical inactivity, depression, low social contact, hearing loss, traumatic brain injury and air pollution indicating clear prevention potential. Dementia and physical disability are closely linked with shared risk factors and possible shared underlying mechanisms supporting the possibility of integrated preventive interventions. FINGER trial was the first large randomized controlled trial indicating that multidomain lifestyle‐based intervention can prevent cognitive and functional decline amongst at‐risk older adults from the general population. Within the World‐Wide FINGERS network, the multidomain FINGER concept is now tested and adapted worldwide proving evidence and tools for effective and easily implementable preventive strategies. Close collaboration between researchers, policymakers and healthcare practitioners, involvement of older adults and utilization of new technologies to support self‐management is needed to facilitate the implementation of the research findings. In this scoping review, we present the current scientific evidence in the field of dementia and disability prevention and discuss future directions in the field. Abstract :